Odpowiedzi

2009-10-01T18:44:27+02:00
A1 = -0,15
a3 = -6

a3 = a1 * q²
-0,15 * q² = -6
q² = 40
q = √40 = 2 √10

a2 = a1 * q = -0,15 * 2 √10 = -0,3 √10
6 3 6
2009-10-01T19:12:42+02:00
Rozwiązanie

Mamy
a₁ = -0,15 , a₃ = -6 , z własności ciągu geometrycznego mamy ,że

a₃(trzy)= a₁q² , q- iloczyn ciągu geomet.

-6 = -0,15 * q² /: (-0,15)

40 = q²/ pierwiastkujemy

q = 2√ 10 zatem
a₃ = -0,15 * 2√10 = - 0,3 √10.
6 2 6
2009-10-01T20:13:03+02:00
-0,15;a₂;-6
a₂:(-0,15) = -6:a₂
(a₂)²=(-0,15)*(-6)
(a₂)²=0,9
a₂=√0,9 lub a₂ =-√0,9

3 2 3